Effects of probiotic supplementation with high-intensity interval training on cardiorespiratory endurance and metabolism in Middle-Aged Obese Women - Yi-Chen Chen; Hsuan-Yun Wang; Futoshi Ogita; Chi-Hsiang Hung; Chia-Hua Kuo; Jie-Ping Wang; Chia-Min Wang; Chien-Wen Hou; Ting-Yao Wang (Journal of the International Society of Sports Nutrition)
Introduction High-intensity interval training (HIIT) has been shown to improve chronic diseases. Probiotics have been found to have similar effects. However, the additive effects of HIIT in combination with probiotics supplementation are unclear. The aim of current study was to investigate whether there were additive effects when implementing both HIIT and probiotics simultaneously.Methods Forty-seven obese middle-aged women (Age: 44.5 ± 5.94 years, body fat percentage: 40.0 ± 4.1%) were recruited and assigned into four groups: control group (C, n = 12), probiotics group (P, n = 12), HIIT group (H, n = 11), and HIIT with probiotics group (HP, n = 12). All the participants consumed probiotics (Lactiplantibacillus plantarum TWK10, 6 × 1010 CFU/day) or placebo supplements daily. Exercise intervention groups conducted HIIT training (85–90% vVO2max for 2 min, followed by a 1-min inactive rest interval, repeated for 7 cycles) 3 sessions per week for 8 weeks. Anthropometry, cardiorespiratory endurance, blood glucose, and lipid profile were measured at baseline and after the 8-week intervention.Results After the intervention, there were significant changes between groups in the variations and rates of change in waist circumference, hip circumference, and TTE. The waist circumference in group H significantly increased compared to groups C and P, while group HP did not show significant difference compared to group C. On the other hand, the hip circumference decreased significantly in group HP compared to group C, and the decreased rate in group HP was significantly greater than in groups C and P. Furthermore, the increase rates in TTE were higher in group H and HP compared to group C.Conclusion HIIT improves TTE but negatively affects waist circumference compared to the control group. However, when combined with probiotics, the probiotics not only help enhance TTE but also counteract the negative impact on waist circumference and further reduce hip circumference, resulting in a synergistic effect.Clinical trial registration ClinicalTrials.gov, identifier NCT06285578